Social media as platforms for the visibility of gender-based violence during the COVID-19 pandemic in Colombia - Doris Elena Muñoz-Zapata; Johanna Marcela Osorio-Franco (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2024)
The purpose of this research is to identify predominant problematizations in Colombian feminist Instagram accounts regarding gender-based violence during the first year of the COVID-19 pandemic. Employing a qualitative approach, a digital ethnography based on the principles of netnography was conducted as an alternative to detail the social worlds constructed from online groups. Fifty pieces of content from @lainsumisa and twenty pieces of content from @feministasenconstrucción, published between March 2020 and March 2021, were selected based on observations made within the online fieldwork framework. These were analyzed using discourse analysis techniques. The findings discuss the following emerging categories: unpaid household work, romanticized harassment, fatphobia, and the violation of Black and racialized women's rights. In this context, cyberactivism is presented as an opportunity for the emergence of collectives and support networks for women advocating for gender equality and their rights, towards questioning patriarchal ideas that jeopardize their well-being.